Estimating pVO2 and prognosis through cardiac exercise stress test in a heart failure population. (14th October 2021) - De Almeida, J.P.L; Milner, J; Rosa, J; Coutinho, R; Ferreira, M; Goncalves, L
Abstract: Background: Compared with the cardiac exercise stress test, more commonly used to assess the presence of ischemia, the cardiopulmonary exercise test has the advantage of providing expired gas analysis. According to current guidelines, cardiopulmonary exercise testing should be considered to stratify the risk of adverse events and to provide measures of survival improvement in heart failure populations. However, cardiac exercise stress test is more readily available and widespread than cardiopulmonary exercise testing. We aimed to compare prognostic information given by estimated pVO2 – which can be obtained from cardiac exercise stress test – and real measured pVO2 – which requires cardiopulmonary exercise test – in a heart failure population. Methods: We conducted a retrospective analysis of 214 patients with HF underwent cardiac exercise stress test and accessed their 5 year survival. Non-urgent transplanted (UNOS Status 2) patients were censored alive on the date of the transplant. Duringthe cardiopulmonary exercise test, cardiac exercise stress test data simultaneously collected. Based on protocol stage achieved, estimated METs were used to calculate estimated pVO2 (pVO2 = estimated METs x 3.5). Estimated and real pVO2 were correlated using Pearson correlation and the age-adjusted prognostic power of each was determined using Cox proportional hazardsanalysis. Results: 164 patients were male (77%) and the mean age of the population was 56±10 years. 78 (36%) patients had an ischemic etiology. Within 5 years from testing, 46 patients died (21.5%) and 55 patients (26%) were transplanted. Naughton modified (n=165) was the most commonly used protocol, followed by Naughton (n=39) and Bruce (n=10). Estimated pVO2 and measured pVO2 correlated significantly (R=0.66, p<0.01) (Figure 1). Both estimated (HR=0.91, 95% CI 0.86–0.95, p<0.01) and measured pVO2 (HR=0.86, 95% CI 0.80–0.91, p<0.01) strongly predicted prognosis in this population. Conclusions: Estimated pVO2 correlated with measured pVO2 and strongly predicted prognosis in this heart failure population. Because it can be obtained from conventional cardiac exercise testing, it may become an alternative prognostic tool to cardiopulmonary testing. Funding Acknowledgement: Type of funding sources: None.